THE INFLUENCE OF HEALTH EDUCATION ON ATTITUDES IN PREVENTING HIV/AIDS TRANSMISSION IN ADOLESCENTS - Sri, Nina; Andini, Delvira (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
These days, pre-sexual conduct stemming from promiscuity has become the norm for youths. Teens are more likely to be infected with HIV/AIDS and other STDs due to their lack of awareness of potential risks associated with sexual activity. The purpose of this study is to determine how health education affects teenagers' perspectives on stopping the spread of HIV/AIDS. This study was carried out at SMAS Riyadlul Jannah using a quasi-experimental one-group pre-post test design with quantitative research. In total, 74 persons were selected utilizing proportionate stratified random sampling and probability sampling procedures, with the study's population consisting of 286 students at SMAS Riyadlul Jannah. The Paired T Test is used to examine the primary data for the study, which was gathered through a questionnaire. The results of the research indicated that teens' excitement for stopping the spread of HIV/AIDS was influenced by health education (Pvalue=0.000). Teenagers' attitudes ranged from 59.51 to 78.24 on average before receiving health education to after receiving it. The goal of health education is to help people maintain and improve their own health by giving them the knowledge, attitudes, and practices they need Key words: HIV/AIDS, Education, Health, Adolescents